Interactions of monovalent salts with cationic lipid bilayers - Pokorna, Sarka; Jurkiewicz, Piotr; Cwiklik, Lukasz; Vazdar, Mario; Hof, Martin (Faraday discussions, 2013)
The influence of monovalent salts (NaF, NaCl, NaBr, NaClO4, KCl) on the properties of lipid bilayers composed of binary mixtures of zwitterionic DOPC (dioleoylphosphatidylcholine) and cationic DOTAP (dioleoyltrimethylammoniumpropane) is experimentally measured and numerically simulated. Both approaches report a specific adsorption of the studied anions at the cationic bilayer. The adsorption is enhanced for higher content of DOTAP in DOPC/DOTAP mixtures and for larger anions (Br and ClO4-). The nonmonotonic dependence of the lipid headgroup mobility, determined using time-dependent fluorescence shifts of Laurdan located at the bilayer carbonyl level, on the content of cationic lipid is preserved in all examined salt solutions. Its maximum, however, is shifted towards higher DOTAP concentrations in the row: NaF < NaCl < NaBr. The same ordering of salts is found for the simulated area per lipid and the measured rigidification of pure DOTAP bilayers. Simulations reveal that Br strongly binds to the cationic headgroups of DOTAP neutralising the bilayer, which induces lateral inhomogeneities in the form of hydrophilic and hydrophobic patches at the membrane-water interface for pure DOTAP. In the equimolar DOPC/DOTAP mixture the neutralising effect of Br results in bending of the PC headgroups to a bilayer-parallel orientation. F-, while attracted to the DOTAP bilayer, has an opposite effect to that of Br-, i.e. it increases local mobility at the lipid carbonyl level. We attribute this effect to the disruption of the hydrogen-bonded structure of the molecules of lipids and water caused by the presence of the adsorbed F-.
Keywords: fluorescenční spektrometrie; simulace molekulární dynamiky; Lipid Bilayers; kationty; Salts; Cations; lipidové dvojvrstvy; Spectrometry, Fluorescence; Molecular Dynamics Simulation; soli